Literarne definicije ljubezni - Virant, Špela (Primerjalna književnost, 2016)
Definitions of love in fiction imitate a rational, scientific approach to the question, what love is. The analysis of chosen passages shows that in this way they - in contrast to non-fictional definitions - enhance the ambiguity of the word love and subvert the dualistic thinking of reason and emotion.
Keywords: German-language literature; nemška književnost; angleška književnost; literarni diskurz; ljubezen; love; definicije ljubezni